Im Steilhang - der jüdische Friedhof zu Adelebsen Erinnerung an eine zerstörte Gemeinschaft - Schaller, Berndt (Universitätsverlag Göttingen, 2010)
The "Flecken Adelebsen" at the edge of the "Solling" in southern Lower-Saxony looks back to 300 years of jewish history. In 19th century it was named "Little Jerusalem" because of the high number of jewish habitants. Today only the jewish graveyard has outlived. The aim of this documentation is to tap this "House of Living" as a new historical resource and do a part of an outstanding and necessary mourning work.